Opening Doors to Independence: Why Your Child’s IEP Should Include Recreational Therapy for Leisure Skills - Archambault, MaryJo; Terpstra, Judy (PALAESTRA, 2026)
Leisure, as the pursuit of activities we choose to engage in during our free time, holds immense potential for enriching our lives. However, individuals with disabilities often face barriers that hinder their ability to participate fully in leisure activities. The delivery of leisure education to students in Special Education is of paramount importance in promoting independence and quality of life. This exploratory study investigates the delivery of leisure education to students in transition programs, aiming to understand current practices. In addition, this paper makes an argument for the inclusion of recreational therapists in the transition setting and encourages guardians to request recreational therapy as a related service on their child’s Individual Education Plan (IEP).
Keywords: dept.rec; dept.sed

Wilderness, workforce, and the paradox of purpose: an exploration of the NPS employee experience - Carroll, Sara; Milone, Joseph (Journal of Outdoor Recreation Education and Leadership, 2026)
Keywords: Exploratory research; Face (sociological concept); Job insecurity; Organizational culture; Public service; Qualitative research; Service (business); Work (physics); dept.rec

Interprofessional education and collaborative practice task force: recommendations from an exploratory study - Bright, Heather; Archambalt, Mary; Ramella, Kelly; Warden, Kylee; Montgomery, Susan (Therapeutic Recreation Journal, 2025)
Keywords: Applied psychology; Engineering; Exploratory research; Medical education; Medicine; Political science; Psychology; Recreation; Social science; Sociology; Task (project management); Task force; dept.rec

Examining effective parenting approaches to promote healthy technology use in children: a systematic review - Gagliardi, Jeffrey; O’Brien, Kyle (Journal of Family Social Work, 2025)
Keywords: Clinical psychology; Developmental psychology; Digital literacy; Psychology; dept.rec; parenting strategies; screen time; technology addiction; technology use

The Situation With Modern Leadership Stacking: Racial Politics, Racial Discourse, and the Realities for Black American Coaches—Who Keeps Moving the Goalposts? - Harrison, C.; Mebane, Karreem; Fennell, Marcis; Griffin, Whitney; McAllister, Dre; Hart, Richard; McArdle, Danielle (Kinesiology Review, 2025)
Keywords: Black male; Gender studies; Law; NFL hiring practices; Political science; Politics; Psychology; Race (biology); Racial bias; Rooney Rule; Social psychology; Sociology; coaching pipeline; dept.rec; peer-reviewed; racial stacking

Dismantling Occupational Therapy Provider Licensure Barriers for Individuals Who Are Underdocumented - O’Brien, Kyle; Miller-Kuhaneck, Heather (American Journal of Occupational Therapy, 2025)
Keywords: Business; Certification; Licensure; Medical education; Medicine; Occupational therapy; Political science; Public relations; Workforce; dept.rec

The Occupation of Play - Bundy, Anita; Kuhaneck, Heather (The American Journal of Occupational Therapy, 2024)
The articles for the Special Section on Play highlight the complexity of play and the many ways occupational therapy practitioners study and promote play with children, families, and adults across individual, school, family, political, and cross-cultural settings. The authors of the articles in this issue view the importance of play across the lifespan and through multiple research lenses, including play preference, environmental supports for and barriers to play, the skills required to succeed in play, and the extent to which play is self-determined. The guest editors offer suggestions for how to enhance occupational therapy’s voice in the study and promotion of play as a primary lifelong occupation.
Keywords: dept.rec; peer-reviewed

Play as occupation: The state of our science and a research agenda for the profession - Kuhaneck, Heather; Bundy, Anita; Fabrizi, Sarah; Lynch, Helen; Moore, Alice; Román-Oyola, Rosa; Stagnitti, Karen; Waldman-Levi, Amiya (The American Journal of Occupational Therapy, 2024)
Occupational therapists view play through a unique lens. Considering play as a human occupation, and one to which all people have a right, places occupational therapists among a special group of professionals championing play. This State of the Science article seeks to increase awareness regarding the occupational therapy profession’s contributions and to situate those contributions within the larger body of literature on play while also promoting further study of play as an occupation.
Keywords: dept.rec; peer-reviewed

The importance of conceptual origins: The case of the just-right challenge - Kuhaneck, Heather; Spitzer, Susan L. (The American Journal of Occupational Therapy, 2024)
Core concepts in occupational therapy have often developed over time with contributions from multiple clinicians and scholars. This makes it difficult to determine exactly from where, or from whom, ideas originated. Without original sources, we cannot chart the historical development of ideas and honor those whose scholarship made it possible. This article documents the process undertaken to properly cite one such common concept in occupational therapy, the just-right challenge; illustrates the value of doing so; and advocates for the importance of thorough historical scholarship.
Keywords: dept.rec; peer-reviewed

Leisure and Tolerance—An Historical Perspective - DeLisle, Lee J. (World Leisure Journal, 2004)
The purpose of this paper is to explain and explore the concept of tolerance as developed in post-Reformation Europe. The religious turmoil of this period tested the social order of the day and will be used to exemplify the difficulties of embracing tolerance while clinging to dogma. The work of French philosopher, Voltaire, provides the reader with an understanding of the Enlightenment's perspective on tolerance as an outgrowth of the repression of the reformation period. Tolerance, in the traditional sense, is limited to the allowance for diverse systems of ideas, beliefs and practices. Tolerance is differentiated from diversity, as a contemporary description of sensitivity to and appreciation of personal difference, and multiculturalism, an all—inclusive attempt to embrace ethnic and racial differences. Tolerance as a contributing factor to cultural progression has profound implications for the continuing evolution of leisure theory. Leisure, both substantively and functionally, requires and supports the notion of tolerance and its subcategories of diversity and multiculturalism.
Keywords: dept.rec; diversity; horror religiosus; multiculturalism; peer-reviewed; religion; tolerance

Analysis of AAHPERD Research Abstracts Published under Special Populations From 1968 to 2004 - Zhang, Jiabei; deLisle, Lee; Chen, Shihui (Adapted Physical Activity Quarterly, 2006)
The purpose of this study was to explore historical research trends in adapted physical activity by analyzing abstracts published under special populations by AAHPERD conventions from 1968 to 2004. There were 562 abstracts retrieved that were coded into seven categories: (a) number of authors, (b) data source, (c) sample size, (d) disability type, (e) data analysis, (f) type of study, and (g) focus of study. The coded data are presented as descriptive statistics and linear regression equations. The results of descriptive statistics describe an overall picture of the knowledge accumulation in adapted physical activity. The results of linear regression equations reveal a number of trends over the 37-year period. These trends suggest that adapted physical activity is a growing profession distinguished by several important research directions.
Keywords: dept.rec; peer-reviewed

Student Self-Management through Contract Administration - deLisle, Lee J. (SCHOLE: A Journal of Leisure Studies and Recreation Education, 2006)
(2006). Student Self-Management through Contract Administration. SCHOLE: A Journal of Leisure Studies and Recreation Education: Vol. 21, No. 1, pp. 149-153.
Keywords: dept.rec; peer-reviewed

Leisure History and Heritage - Delisle, Lee J. (Dimensions of Leisure for Life: Individuals and Society, 2010)
Keywords: dept.rec

Estándares de gestión en centros fitness de la región sur de Connecticut desde el punto de vista del gestor: Estudio piloto - León Quismondo, Jairo; García Unanue, Jorge; Burillo, Pablo; Delisle, Lee J. (Economía, gestión y deporte: Una visión actual de la investigación, 2016, ISBN 978-84-9135-160-3, págs. 85-88, 2016)
Keywords: dept.rec

Is Talking About What’s Wrong Necessarily Right: A Positive Perspective on the Diagnostic Interview - O’Brien, Kyle H.; Schlechter, Alan (Journal of the American Academy of Child & Adolescent Psychiatry, 2016)
Keywords: Adolescent; Child; Child Psychiatry; Emotions; Humans; Interview, Psychological; Mental Disorders; Neurodevelopmental Disorders; dept.rec; dept.swk; peer-reviewed

A model of integrated health care in a poverty-impacted community in New York City: Importance of early detection and addressing potential barriers to intervention implementation - Acri PhD, Mary C.; Bornheimer MS, LCSW,Lindsay A.; O’Brien DHSc, MSW, MSOT, LCSW, OTR/L,Kyle; Sezer MPA, Sara; Little PsyD, LCSW-r, SAP, CCM,Virna; Cleek PhD, Andrew F.; McKay PhD, Mary M. (Social Work in Health Care, 2016)
Disruptive behavior disorders (DBDs) are chronic, impairing, and costly behavioral health conditions that are four times more prevalent among children of color living in impoverished communities as compared to the general population. This disparity is largely due to the increased exposure to stressors related to low socioeconomic status including community violence, unstable housing, under supported schools, substance abuse, and limited support systems. However, despite high rates and greater need, there is a considerably lower rate of mental health service utilization among these youth. Accordingly, the current study aims to describe a unique model of integrated health care for ethnically diverse youth living in a New York City borough. With an emphasis on addressing possible barriers to implementation, integrated models for children have the potential to prevent ongoing mental health problems through early detection and intervention.
Keywords: Child mental health; dept.rec; dept.swk; early detection and treatment; integrated care pathway; peer-reviewed

Parental Mental Health: Addressing the Unmet Needs of Caregivers for Children With Autism Spectrum Disorders - Lushin, Viktor; O’Brien, Kyle H. (Journal of the American Academy of Child & Adolescent Psychiatry, 2016)
Keywords: dept.rec; dept.swk; peer-reviewed

Development of the Sensory Processing Measure–School: Initial Studies of Reliability and Validity - Miller-Kuhaneck, Heather; Henry, Diana A.; Glennon, Tara J.; Mu, Keli (The American Journal of Occupational Therapy, 2007)
OBJECTIVE. The history and development of the Sensory Processing Measure–School are detailed, and findings of initial pilot studies are reported.METHOD. Multiple reviews, focus groups, case studies, and two pilot studies were used to develop the early versions of the tool. Internal consistency and discriminatory ability were examined.RESULTS. Internal consistency measured with Cronbach’s alphas ranged from .93 to .99 in the first pilot study and .70 to .99 in the second pilot study. Children who were typically developing were correctly classified 92.3% of the time, and children with sensory issues were correctly classified 72% of the time.CONCLUSION. Initial results suggest that the tool is reliable and valid and discriminates children with and without sensory processing issues. Further research is under way with larger samples.
Keywords: dept.rec; peer-reviewed

Play Preferences of Typically Developing Children and Children with Developmental Delays between Ages 3 and 7 Years - Case-Smith, Jane; Kuhaneck, Heather Miller (OTJR: Occupational Therapy Journal of Research, 2008)
This cross-sectional survey research investigated play preferences of children with and without developmental delays who were between 3 and 7 years old. Parents completed questionnaires regarding their child's play activity and context preferences. Valid results were obtained for 166 children, 83 of whom had developmental delays. Preference ratings were compared by gender, age, and delay status. Play preference did not differ by gender. Rough-and-tumble play and computer/video game play increased with age, whereas object exploration decreased. Children with developmental delays had higher preferences for rough-and-tumble play and object exploration and lower preferences for drawing and coloring, construction, and doll and action figurine play than typically developing children. This comparison of children's play preferences across ages, gender, and developmental status enhances our understanding of how these variables influence children's play.
Keywords: dept.rec; peer-reviewed

Children’s Perceptions of Play Experiences and Play Preferences: A Qualitative Study - Miller, Elissa; Kuhaneck, Heather (The American Journal of Occupational Therapy, 2008)
This qualitative study investigated the perceptions of play experiences and rationales for play choices of 6 boys and 4 girls between the ages of 7 and 11 years. Individual in-depth interviews were completed and then transcribed, and the transcripts were coded and analyzed using grounded theory methodology. Fun emerged from the data as the core category explaining the choice of specific play activities for children, and 4 additional categories of characteristics surfaced as contributors to the children’s perception of fun: relational, activity, child, and contextual. The relationships among the core category, the 4 characteristics categories, and the development of play preference and meaningfulness are illustrated in the Dynamic Model for Play Choice. Included is a discussion of the usefulness of the model in supporting the careful consideration of factors that will increase the perception of fun during therapeutic activities and facilitate client-centered pediatric practice.
Keywords: dept.rec; peer-reviewed

The Sensory Processing Measure (SPM): Meeting the Needs of School-Based Practitioners Part One: Description and Background - Miller Kuhaneck, Heather; Henry, Diana A. (Journal of Occupational Therapy, Schools, & Early Intervention, 2009)
Changes in federal legislation guiding occupational therapy practice in educational environments have required modifications in the way therapists evaluate children in these settings. New methods in turn require new tools. This article will describe one new tool designed to assist school-based practitioners in their assessment of the impact of sensory processing and praxis difficulties on educational performance. The Sensory Processing Measure is an assessment tool that promotes team collaboration by examining performance across multiple natural environments and also considers the relationship between sensory processing, praxis and social participation. Part One of this paper provides a description of the assessment tool and its proposed uses while in Part Two, examples of the use of the measure will be presented.
Keywords: Assessment; dept.rec; peer-reviewed; school-based practice; sensory processing

A Qualitative Study of Coping in Mothers of Children with an Autism Spectrum Disorder - Kuhaneck, Heather Miller; Burroughs, Tajhma; Wright, Jamie; Lemanczyk, Theresa; Darragh, Amy Rowntree (Physical & Occupational Therapy In Pediatrics, 2010)
A significant body of research exists that explores the stressors of raising a child with an autism spectrum disorder (ASD). There are fewer studies, however, that examine specific effective coping strategies of mothers of children with an ASD. This qualitative study explored mothers’ perceptions of effective coping strategies for their parenting stressors. In-depth interviews were conducted with 11 mothers to inquire about their personal coping methods. Interviews were coded and emergent themes identified that included coping strategies such as “me time,” planning, knowledge is power, sharing the load, lifting the restraints of labels, and recognizing the joys. The information from this study may benefit mothers of children with ASD and inform pediatric therapists providing services to children with ASD and their families.
Keywords: Autistic spectrum disorders; coping strategies; dept.rec; mothers; parenting stress; peer-reviewed; qualitative

The Sensory Processing Measure–Preschool (SPM-P)—Part One: Description of the Tool and Its Use in the Preschool Environment - Glennon, Tara J.; Miller Kuhaneck, Heather; Herzberg, David (Journal of Occupational Therapy, Schools, & Early Intervention, 2011)
School-based and early intervention occupational therapy evaluation is influenced by federal policy and prevailing ideas regarding best practice. Current best practice considers a child's performance in appropriate contexts and natural environments, as well as the impact of the environment on occupational functioning and participation across settings. As a recent report suggested 3.4% to 15.6% of children in a community sample of 4-year-olds may demonstrate sensory processing difficulties, occupational therapists should be familiar with multiple methods of assessment to address these concerns. One such assessment tool, the Sensory Processing Measure–Preschool (SPM-P) for children 2- to 5-years old, provides 8 scaled scores: Vision, Hearing, Touch, Body Awareness, Balance and Motion, Total Sensory System Score, Planning and Ideas, and Social Participation. Through discussion on the development, usage, and implementation of both Home and School forms, this article illustrates how the SPM-P provides a mechanism for preschool educational teams to meet best practice initiatives.
Keywords: Sensory; assessment; collaboration; context; dept.rec; peer-reviewed; preschool

Improving dental visits for individuals with autism spectrum disorders through an understanding of sensory processing - Kuhaneck, Heather Miller; Chisholm, Elizabeth Cipes (Special Care in Dentistry, 2012)
The increasing prevalence of autism spectrum disorder (ASD) suggests that dental practices will be seeing patients with this diagnosis more frequently. Although patients with ASD have similar dental needs to other patients, the symptoms of the disorder may influence the ability of dental practitioners to provide necessary care. Dental professionals may be unaware of the difficulties with sensory processing common to patients with ASD. However, awareness of sensory processing issues and knowledge of strategies to improve the sensory experience for individuals with ASD may improve dental visits for these patients and allow for enhanced dental care provision.
Keywords: autism; autism spectrum disorder; dept.rec; peer-reviewed; sensory processing; sensory strategies; special care dentistry

A Preliminary Investigation of the Relationship between Sensory Processing and Social Play in Autism Spectrum Disorder - Kuhaneck, Heather Miller; Britner, Preston A. (OTJR: Occupational Therapy Journal of Research, 2013)
There are well-documented play deficits in autism beginning with infant object and social play. To create effective interventions, the predictors of play deficits in autism must be established. Individuals with autism spectrum disorder (ASD) frequently report sensory processing difficulties including poor praxis; however, these are potential predictors of play that have not been well studied. Using a data set of 162 individuals with ASD, this study examined the direct and indirect relationships between sensory processing and social play performance via structural equation modeling. The best fitting model suggested that sensory system functions predict praxis and play in combination, providing preliminary evidence that sensory functions are related to social play in combination with praxis in children with ASD. The findings suggest future avenues for research.
Keywords: dept.rec; peer-reviewed

A Survey of Pediatric Occupational Therapists' Use of Play - Miller Kuhaneck, Heather; Tanta, Kari J.; Coombs, Allison Kristine; Pannone, Heather (Journal of Occupational Therapy, Schools, & Early Intervention, 2013)
Over a decade ago, researchers surveyed pediatric occupational therapists regarding their use of play and concluded that play was addressed inconsistently in the evaluation and treatment of preschool-age clients. Play was primarily used as a modality to achieve a desired performance in another skill area. In the intervening years, a significant body of literature has been published in occupational therapy promoting the use of play as a meaningful outcome of occupational therapy intervention; therefore, practice patterns may have changed. Five hundred pediatric occupational therapists were randomly selected from members of the school system and sensory integration special interest sections of the American Occupational Therapy Association (AOTA) to be surveyed regarding their current usage of play with children ages 3 to 7 years. They received a mailed survey, adapted from the original work of Couch, Dietz, and Kanny with the permission of the primary author. There were 198 surveys returned (40%). Similar to earlier findings, play was used primarily as a means of eliciting improvement in another area, such as fine-motor skill. Although some therapists assessed play, few focused on play as an outcome of importance, or included goals for play. Minimal changes have occurred in the role of play in pediatric occupational therapy. Despite the profession's promotion of our role in play and the suggestion that play is one of the most important occupations of childhood, practitioners continue to report a limited focus on play as an occupation.
Keywords: Play assessment; dept.rec; play intervention

Evolution of a Theory: How Measurement Has Shaped Ayres Sensory Integration® - Mailloux, Zoe; Miller-Kuhaneck, Heather (The American Journal of Occupational Therapy, 2014)
Scientific theory evolves through phases. Scientists observe phenomena, classify their observations, examine and explain causation, and attempt to understand their results in varied circumstances. If anomalies are found that do not mesh with the theory, revision occurs, and the theory is improved (Christensen, Carlile, & Sundahl, 2001). Each stage requires accurate and precise measurement and, therefore, appropriate measurement tools.The body of scientific inquiry developed by A. Jean Ayres is deeply rooted in systematic and methodical measurement, and her work marked the first effort by an occupational therapist to build a theory for clinical application with an evidence-based approach. The trajectory of the growth of Ayres Sensory Integration® (ASI), beginning in the 1950s with continual advancements from the ongoing contributions of the researchers who have built on her seminal work since that time, has occurred simultaneously with the widespread use of more rigorous research methods, attention to measurement of fidelity, greater usage of exploratory and factor analysis, and more routine practice of examining multivariate research problems with computer statistical programs (Century, Rudnick, & Freeman, 2010; Elmore & Woehlke, 1988; Keselman et al., 1998; Ottenbacher & Peterson, 1985; Press, 2013; Tukey, 1980; West, Carmody, & Stallings, 1983).
Keywords: dept.rec; peer-reviewed

Effectiveness of Interventions for Children With Autism Spectrum Disorder and Their Parents: A Systematic Review of Family Outcomes - Kuhaneck, Heather Miller; Madonna, Stephanie; Novak, Audrey; Pearson, Emily (The American Journal of Occupational Therapy, 2015)
This systematic review examined the literature published from January 2006 to April 2013 related to the effectiveness of occupational therapy interventions for children with autism spectrum disorder (ASD) and their parents to improve parental stress and self-efficacy, coping, and resilience and family participation in daily life and routines. From the 4,457 abstracts, 34 articles were selected that matched the inclusion criteria. The results were mixed and somewhat inconclusive because this body of literature is in its infancy. Studies of children with ASD do not routinely measure parental and family outcomes. Recommendations include an emphasis on family measures other than parental stress and a greater focus on measures of parental and family functioning in all future studies of pediatric interventions to more fully understand the impact of interventions in a wider context.
Keywords: dept.rec; peer-reviewed

Development of the Classroom Sensory Environment Assessment (CSEA) - Kuhaneck, Heather Miller; Kelleher, Jaqueline (The American Journal of Occupational Therapy, 2015)
The Classroom Sensory Environment Assessment (CSEA) is a tool that provides a means of understanding the impact of a classroom’s sensory environment on student behavior. The purpose of the CSEA is to promote collaboration between occupational therapists and elementary education teachers. In particular, students with autism spectrum disorder included in general education classrooms may benefit from a suitable match created through this collaborative process between the sensory environment and their unique sensory preferences. The development of the CSEA has occurred in multiple stages over 2 yr. This article reports on descriptive results for 152 classrooms and initial reliability results. Descriptive information suggests that classrooms are environments with an enormous variety of sensory experiences that can be quantified. Visual experiences are most frequent. The tool has adequate internal consistency but requires further investigation of interrater reliability and validity.
Keywords: dept.rec; peer-reviewed

Systematic Review of the Effectiveness of Frequency Modulation Devices in Improving Academic Outcomes in Children With Auditory Processing Difficulties - Reynolds, Stacey; Miller Kuhaneck, Heather; Pfeiffer, Beth (The American Journal of Occupational Therapy, 2015)
This systematic review describes the published evidence related to the effectiveness of frequency modulation (FM) devices in improving academic outcomes in children with auditory processing difficulties. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards were used to identify articles published between January 2003 and March 2014. The Cochrane Population, Intervention, Control, Outcome, Study Design approach and the American Occupational Therapy Association process forms were used to guide the article selection and evaluation process. Of the 83 articles screened, 7 matched the systematic review inclusion criteria. Findings were consistently positive, although limitations were identified. Results of this review indicate moderate support for the use of FM devices to improve children’s ability to listen and attend in the classroom and mixed evidence to improve specific academic performance areas. FM technology should be considered for school-age children with auditory processing impairments who are receiving occupational therapy services to improve functioning in the school setting.
Keywords: dept.rec

Using a Multifaceted Approach to Working With Children Who Have Differences in Sensory Processing and Integration - Reynolds, Stacey; Glennon, Tara J.; Ausderau, Karla; Bendixen, Roxanna M.; Kuhaneck, Heather Miller; Pfeiffer, Beth; Watling, Renee; Wilkinson, Kimberly; Bodison, Stefanie C. (The American Journal of Occupational Therapy, 2017)
Pediatric occupational therapy practitioners frequently provide interventions for children with differences in sensory processing and integration. Confusion exists regarding how best to intervene with these children and about how to describe and document methods. Some practitioners hold the misconception that Ayres Sensory Integration intervention is the only approach that can and should be used with this population. The issue is that occupational therapy practitioners must treat the whole client in varied environments; to do so effectively, multiple approaches to intervention often are required. This article presents a framework for conceptualizing interventions for children with differences in sensory processing and integration that incorporates multiple evidence-based approaches. To best meet the needs of the children and families seeking occupational therapy services, interventions must be focused on participation and should be multifaceted.
Keywords: dept.rec

Parental or Teacher Education and Coaching to Support Function and Participation of Children and Youth With Sensory Processing and Sensory Integration Challenges: A Systematic Review - Miller-Kuhaneck, Heather; Watling, Renee (The American Journal of Occupational Therapy, 2017)
This systematic review examines the literature published from January 2007 through May 2015 related to the effectiveness of occupational therapy interventions using parental or teacher education and coaching with children with challenges in sensory processing and sensory integration (SP–SI). Of more than 11,000 abstracts and 86 articles that were considered, only 4 met the criteria and were included in this review. Studies of parental training and coaching for children with challenges in SP–SI and comorbid autism spectrum disorder have suggested that educational or coaching programs could result in positive outcomes for both parents and children, often in a relatively short time period. Recommendations include a greater focus on providing educational interventions for parents and teachers and including specific assessment of SP–SI before implementing interventions meant to address those issues. Specific recommendations for future research are provided.
Keywords: dept.rec; peer-reviewed

The classroom sensory environment assessment as an educational tool for teachers - Kuhaneck, Heather; Kelleher, Jacqueline (Journal of Occupational Therapy, Schools, & Early Intervention, 2018)
The Classroom Sensory Environment Assessment (CSEA) is a tool that provides a format for examining the sensory environment of a classroom and considering its impact on student behavior and performance. The purpose of the CSEA is to promote awareness of classroom sensory experiences for general elementary education teachers and to aide collaboration between occupational therapists and teachers. This qualitative study investigated the perceived usefulness of the CSEA for general educators and preservice teachers. The resultant themes included “the process led to greater awareness,” “driven to distraction,” and “the sights and sounds of a classroom.” The results support the potential use of the CSEA as a method of generating greater understanding for teachers regarding sensory processing and the sensory experiences present in their classrooms.
Keywords: Sensory processing; assessment; classroom environment; dept.rec

Cognition, Cognitive Rehabilitation, and Occupational Performance - Giles, Gordon Muir; Radomski, Mary Vining; Wolf, Timothy J.; Kuhaneck, Heather (American Journal of Occupational Therapy, 2019)
The American Occupational Therapy Association (AOTA) asserts that occupational therapists and occupational therapy assistants, through the use of occupations and activities, facilitate clients' cognitive functioning to enhance occupational performance, self-efficacy, participation, and perceived quality of life. Cognitive processes are integral to effective performance across the broad range of daily occupations such as work, educational pursuits, home management, and play and leisure. Cognition plays an integral role in human development and in the ability to learn, retain, and use new information to enable occupational performance across the lifespan. This statement defines the role of occupational therapy in evaluating and addressing cognitive functioning to help clients maintain and improve occupational performance. The intended primary audience is practitioners1 within the profession of occupational therapy. The statement also may be used to inform recipients of occupational therapy services, practitioners in other disciplines, and the wider community regarding occupational therapy theory and methods and to articulate the expertise of occupational therapy practitioners in addressing cognition and challenges in adapting to cognitive dysfunction.
Keywords: American Occupational Therapy Association; Cognition; Cognition Disorders; Functional Assessment; Human Development; Interprofessional Relations; Job Characteristics; Job Performance; Occupational Therapists; Occupational Therapy -- Standards; Occupational Therapy Assistants; Occupational Therapy Service; Professional Development; Quality of Life; Rehabilitation, Cognitive; dept.rec; peer-reviewed

Diagnostic Statistical Manual 5 Changes to the Autism Diagnostic Criteria: A Critical Moment for Occupational Therapists - Whitney, Rondalyn; Miller-Kuhaneck, Heather (The Open Journal of Occupational Therapy, 2012)
Keywords: dept.rec; peer-reviewed

Etiology of ASD - Kuhaneck, Heather M. (Autism Across the Lifespan: A Comprehensive Occupational Therapy Approach, 2018)
Keywords: dept.rec

Applying Principles of Family-Centered Care With Families of Individuals With ASD - Kuhaneck, Heather M.; Luthman, M. (Autism Across the Lifespan: A Comprehensive Occupational Therapy Approach, 2018)
Keywords: dept.rec

Positive Youth Development: Minority Male Participation in a Sport-Based Afterschool Program in an Urban Environment - Fuller, Rhema D.; Percy, Vernon E.; Bruening, Jennifer E.; Cotrufo, Raymond J. (Research Quarterly for Exercise and Sport, 2013)
Purpose As there is little research that investigates the experiences of minority boys participating in youth development programs (Fashola, 2003), the current research focused on a sport-based youth development program for early adolescent Black and Latino boys in Hartford, CT. Specifically, the present study explored (a) what attracted minority boys to participate in youth development programs, (b) what kept them involved, and (c) whether their involvement translated into positive developmental outcomes. Method The study used semistructured individual interviews to collect data from 8 participants and their parents. The research team deductively coded interviews in accordance with the a-priori framework of the Five Cs and Sixth C of youth development (i.e., competence, character, caring, confidence, connection, and contribution; Roth & Brooks-Gunn, 2003). In addition, interviews were deductively coded to investigate why participants became involved in the program and why they continued participation. Results Findings from the study indicated that participants became involved with the Sport Hartford Boys (SHB) program mainly due to its emphasis on sport-related activities. Moreover, findings related to the youths' continued involvement revealed their value for the SHB program as a safe place that kept them out of trouble and provided experiences that led to positive personal development. Furthermore, results indicated that participation in the program facilitated the development of each “C” of youth development. Conclusion By promoting positive relationships and providing opportunities for self-exploration in a safe and trusting environment, afterschool programs can cultivate positive youth development in minority boys, at least in the short term.
Keywords: dept.rec; identity development; mentoring; peer-reviewed; sport-based youth development; youth programs

The Ultimate Penalty Box: Fayetteville-Manlius is Disqualified from the State Playoffs for Playing Too Many Games: Editor: Thomas H. Sawyer - Dodds, Mark A.; Cotrufo, Raymond J. (Journal of Physical Education, Recreation & Dance, 2015)
Instead of playing in the state tournament, the Fayetteville-Manlius boy's hockey team was disqualified because they played too many games. The New York State Public High School Athletic Association limits hockey teams to 20 regular season games, but Fayetteville-Manlius mistakenly considered one of its competitions to be a scrimmage instead of a regular season game.
Keywords: dept.rec; peer-reviewed

Applying Intergroup Contact Theory to the Sport Management Classroom - Bruening, Jennifer; Fuller, Rhema D.; Cotrufo, Raymond J.; Madsen, Rachel M.; Evanovich, Justin; Wilson-Hill, Devon E. (Sport Management Education Journal, 2014)
Allport’s (1954) intergroup contact hypothesis states that interactions with members of an out-group, particularly of a different racial and/or ethnic group, are effective in changing attitudes about diversity (Allport, 1954; Pettigrew, 1998). In this study, the intergroup contact hypothesis was applied to the design of a sport management course. The classroom component focused the role of sport in education, health, and leadership development, and the application was structured sport and physical activity programming with school-age children at several urban sites. Data were gathered from 91 college students over 3 years about course-related experiences and how the students’ backgrounds influenced their social identities and understanding of out-group members. Results showed that intergroup contact effectively assisted in developing understanding and cooperation and reducing negative attitudes between groups. The participants received diversity education, via intergroup contact, both inside and outside the classroom, which will potentially equip them to take proactive strategies when managing organizational diversity in the sport industry.
Keywords: dept.rec

The Experiences of Female Athletic Trainers in the Role of the Head Athletic Trainer - Mazerolle, Stephanie M.; Burton, Laura; Cotrufo, Raymond J. (Journal of Athletic Training, 2015)
Very few women have leadership positions in athletic training (ie, head athletic training positions) in intercollegiate athletics. Research exists on the barriers to attaining the role; however, our understanding about the experiences of those currently engaged in the role is limited.To examine the experiences of female head athletic trainers as they worked toward and attained the position of head athletic trainer.Qualitative study.National Collegiate Athletic Association Division I setting.Eight female athletic trainers serving in the role of head athletic trainer participated in our study. The mean age of the participants was 45 ± 12 years, with 5 ± 1.5 years of experience in the role of head athletic trainer and 21 ± 10 years of experience as athletic trainers.We conducted phone interviews with the 8 participants following a semistructured format. Interviews were transcribed verbatim and analyzed following a general inductive approach as described by Thomas. To establish credibility, we used a peer reviewer, member checks, and multiple-analyst triangulation.Six major themes emerged from our analysis regarding the experiences of female head athletic trainers. Opportunities to become a head athletic trainer, leadership qualities, and unique personal characteristics were discussed as factors leading to the assumption of the role of the head athletic trainer. Where women hold back, family challenges, and organizational barriers speak to the potential obstacles to assuming the role of head athletic trainer.Female head athletic trainers did not seek the role, but through persistence and encouragement, they find themselves assuming the role. Leadership skills were discussed as important for success in the role of head athletic trainer. Life balancing and parenting were identified as barriers to women seeking the role of head athletic trainer.
Keywords: dept.rec; peer-reviewed

NFL Evolution: Does Prioritizing Player Welfare Influence Consumers? - Cotrufo, Raymond J.; Burton, Laura J. (International Journal of Sport Management, 2016)
NFL Evolution is a Corporate Social Responsibility (CSR) program designed to improve the health and safety of football participants at all levels (NFLEvolution. com). Though sport-based CSR initiatives are generally well-received by the public, the internal focus of this particular initiative may affect consumers differently. Using data provided by a sample of university students via an online survey, regression analysis was used to determine if this program affected their intentions to consume NFL-related products and media. Results showed that this form of CSR initiative may influence consumption behaviors, especially related to media consumption and intentions to discuss the NFL with others. ABSTRACT FROM AUTHOR
Keywords: NATIONAL Football League; REGRESSION analysis; SOCIAL responsibility of business; dept.rec

Intercollegiate Athletes - Cotrufo, Raymond J. (Sports Leadership: A Concise Reference Guide, 2015)

Commitment to the Future: The Tour de France Rides for a More Sustainable World - León-Quismondo, J. (Dealing with Socially Responsible Consumers: Studies in Marketing, 2023)
(a) Situation faced: The Tour de France, with more than a century of history, provides great opportunities for raising awareness of socially responsible behaviors among citizens, not only from France but also from other regions in the world; (b) Action taken: The Tour de France is committed to the future. Responsible actions are deployed in three main axons: sustainable transportation, commitment with the charter of 15 eco-friendly commitments, and specific in-route measures; (c) Results achieved: Currently, the Tour de France is a leading sport event in terms of Corporate Social Responsibility. Their actions positively influence large social masses from all over the world; (d) Lessons learned: This case provides good examples of a socially responsible sport event that spreads messages to national and international spectators. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.
Keywords: Awareness; Bicycles; Case study; Cycling; Positive influence; Responsible marketing; Sports events; Sustainable mindset; Tour de France; dept.rec

Exploring First-Generation College Students Leadership Behaviors and Actions during Intramural Sports - Milone, Joseph (Journal of Campus Activities Practice and Scholarship, 2021)
College graduates need to have specific leadership-related skills, behaviors, and traits when entering the workforce. Campus involvement is one way for students to develop such areas. Therefore, this qualitative study explored the self-reported leadership skills of first-generation college students who were actively participating in intramural sports. Twelve students from a 4-year public university in the Northeast were interviewed about the research-driven photographs they submitted depicting leadership skills they engaged in during intramural sports participation. Photograph captions and interviews were analyzed using Kouzes and Posner's (2014) leadership model. Findings revealed that students reported engaging in behaviors and actions aligned with the leadership practices described by Kouzes and Posner (2014). These findings can help inform the decisions campus recreation professionals make about the role leadership development plays in program offerings.
Keywords: First Generation College Students; Intramural Athletics; Leadership Qualities; Photography; Student Attitudes; Student Behavior; Student Leadership; dept.rec; peer-reviewed

Diversifying diversity, equity and inclusion in American college athletics: the case for adaptive (and other non-traditional) sports - McGinniss, K. T.; Goutis, D.; Tuakli-Wosornu, Y (The Sports Journal, 2020)
Keywords: dept.rec; peer-reviewed

Identifying Coach and Institutional Characteristics That Facilitate the Development of NCAA Wheelchair Basketball Programs - Rutland, Emily A.; Suttiratana, Sakinah C.; Huang, Patrick; Ayala, Kimberly E. Ona; McGinniss, Kevin T.; Tuakli-Wosornu, Yetsa A. (Sports Innovation Journal, 2022)
Background: Despite national and institutional policies, American colleges do not currently provide student-athletes with disabilities equal access to sports opportunities. Disabled youth who wish to pursue their academic and athletic dreams in college thus have prohibitively limited options, even with popular American sports such as basketball. Purpose: The purpose of this study was to identify characteristics and factors that may facilitate the development and perpetuation of collegiate wheelchair basketball programs in the United States. Methods: Five qualitative interviews were conducted with coaches and/or program administrators of established college wheelchair basketball programs. Interviews were coded and analyzed to explore common themes. Results: Thematic data analysis uncovered five common themes important to the development and maintenance of these programs: a) coach characteristics, b) actions to recognize and address equity, c) boosters, d) institutional barriers, and e) network effects. Conclusion: These common factors are important in the development, sustainability, and longevity of college wheelchair basketball programs and should be considered by those interested in starting similar programs.
Keywords: Collegiate Sports; NCAA Sports; Para Sport; Wheelchair Basketball; adaptive sports; dept.rec; peer-reviewed

A Systematic Review of Interventions to Improve the Occupation of Play in Children With Autism - Kuhaneck, Heather; Spitzer, Susan L.; Bodison, Stefanie C. (OTJR: Occupational Therapy Journal of Research, 2020)
Play in children with autism spectrum disorder (ASD) is often atypical, yet consensus regarding effective occupational therapy strategies for improving play is not established. To examine the efficacy of strategies used in occupational therapy to improve play in ASD, authors completed a systematic review of papers from January 1980 through January 2019. Search terms included autism, Asperger’s, ASD, autistic in combination with play, playfulness, pretend, imagination, praxis, creativity, and generativity. Twenty papers met inclusion criteria and were reviewed. Reviewed interventions included parent education, modified play materials or environments, imitation of the child, and modeling by an adult, a peer, or video. Moderate to strong support exists for the specific strategies of imitation of the child and modeling for the child, with lesser or mixed support for other strategies. Certain strategies commonly used in occupational therapy may be effective in improving the occupation of play in ASD.
Keywords: dept.rec; peer-reviewed

The Occupational Therapist as a Tour Guide to the Land of "PLAY" - Kuhaneck, Heather (Making Play Just Right: Unleashing the Power of Play in Occupational Therapy, 2022)

Selecting Play Activities through Sound Professional Reasoning - Kuhaneck, Heather (Making Play Just Right: Unleashing the Power of Play in Occupational Therapy, 2022)

Playful Play Spaces - Kuhaneck, Heather (Making Play Just Right: Unleashing the Power of Play in Occupational Therapy, 2022)

Play in School-Based Occupational Therapy - Kuhaneck, Heather (Making Play Just Right: Unleashing the Power of Play in Occupational Therapy, 2022)

Informal Play Assessment and Activity Analysis - Kuhaneck, Heather (Making Play Just Right: Unleashing the Power of Play in Occupational Therapy, 2022)

Contributions of the Profession of Occupational Therapy to the Understanding of the Phenomenon of Play as an Occupation - Kuhaneck, Heather (Making Play Just Right: Unleashing the Power of Play in Occupational Therapy, 2022)

Making Play Just Right: Unleashing the Power of Play in Occupational Therapy - Kuhaneck, Heather; Spitzer, Susan L. (Jones & Bartlett Learning, 2022)
Keywords: dept.rec

Perceptions of NCAA Division II and III Athletic directors regarding the emergence of e-sports - Cotrufo, Raymond J.; MacGregor, James F.; McGinniss, Kevin T. (Journal for the Study of Sports and Athletes in Education, 2022)
This study assessed perspectives of NCAA D-II and D-III Athletics Directors (ADs) regarding the possible implementation of competitive e-Sports on college campuses. It examines if ADs view e-Sports as a legitimate sport in parallel with others that are traditionally offered by athletic departments, and their perspective regarding where on college campuses e-Sports should be housed. Results demonstrated that ADs view e-Sports differently than other sport programs (F = 13.439; p = .001), and this was key in determining where they thought e-Sports programs should be administered (F = 6.696; p = .013). However, some expressed a willingness to consider implementing e-Sports due to the opportunity it could present (F = 2.209; p = .021). These results suggest that an apparent conflict exists between ADs’ perceptions of e-Sports and of its potential as a growth opportunity. However, if colleges decide to implement e-Sports as an athletic program, consideration should be given to governance concerns, budgetary concerns, and the health and wellness of participants.
Keywords: Division II; Division III‌ ‌; E-sports; NCAA; athletic directors; dept.rec; gaming; intercollegiate athletics; peer-reviewed; student affairs

Recreational sport opportunities for youth with disabilities: Perspectives of recreation directors in New England - Macgregor, James; Risisky, Deb; McGinniss, Kevin (Recreational Sport Opportunities for Youth with Disabilities, 2020)
1 2 1 1 2 1/15 Purpose: Inclusive recreation practices are one of the most recognized means of providing recreational sport opportunities for youth with disabilities. Municipal recreation departments are responsible for ensuring opportunities to partake in youth sport programs. This study evaluates the extent to which recreation departments are providing inclusive recreational sport opportunities to individuals with disabilities. Methods: This study employed a cross-sectional design mail survey to gather data from recreation directors across New England. The two dependent variables for this study are provision of inclusive services and perceived challenges to providing those services. The independent variables include director recreation/sport education, years as a director, and community size. Analysis included univariate, bivariate, and ANOVA for the quantitative data. Qualitative data were reviewed for commonalities. Results: There were 136 respondents for a response rate of 34.8%. Most (85%) directors noted their agency provided some inclusive recreation. Areas of success included accessible facilities and accommodations/modifications. Areas of needed improvement included staff training and providing transportation for individuals with disabilities. The only significant factor was years as a Director (F=4.315; p=0.016). The multiple comparison test found statistical significance between those with the fewest years of experience (x=22.14) and highest experience (x=19.57). The top challenges in providing inclusive recreational sport was additional expense, and the lack of training for the provision of these services. Conclusions: Without director support, inclusive recreation can be difficult to achieve. Director support, including making inclusion an agency priority, reflecting inclusion in the agency's mission, and hiring practices was imperative to facilitating an inclusive recreation environment and program. Financial concerns and need for staff training are the biggest obstacles to providing inclusive recreational sport programming. Applications in Sport: Training of recreation and youth sport staff members, including those that aspire to be directors, can have a great impact on opening opportunities for inclusive recreational sports. University academic recreation and sport management programs need to embed the principles and practices of inclusion into their curriculum. In-service training can be an important tool to increase inclusion offerings to the community, increasing the amount of staff members who can facilitate increased opportunities for inclusive recreational sport.
Keywords: dept.pch; dept.rec; peer-reviewed

Answering the Big Questions About Play - Kuhaneck, Heather; O'Brien, K. (Making Play Just Right: Unleashing the Power of Play in Occupational Therapy, 2022)
Keywords: dept.hls

Disruptive Technologies and Innovation in Hospitality: A Computer-Assisted Qualitative Data Analysis Approach - Lee, Minwoo; Sisson, Annamarie D.; Costa, Rui; Bai, Billy (Journal of Hospitality & Tourism Research, 2023)
As emerging digital technologies have been used for disruptive innovation and business models, an essential component for hospitality researchers and practitioners is to determine the role of disruptive technologies and innovation in hospitality businesses. This study synthesizes prior research on disruptive innovation and identifies disruptive technologies in the hospitality context. A thematic analysis was performed through a computer-assisted qualitative data analysis approach using 23 publicly traded hospitality companies. Results reveal that disruptive technology and innovation are among the most critical strategic aspects in contemporary hospitality firms. This study provides contributions to hospitality researchers and practitioners to implement disruptive technologies for superior business performance. This study is among the first to introduce and synthesize disruptive technologies and innovation in the hospitality context.
Keywords: dept.rec; peer-reviewed

Event Planning and Management at Colleges and University: An Emerging Hospitality Profession - Shaw, Suzanne (Kendall Hunt Publishing Company, 2021)
Event Planning & Management At Colleges & Universities: An Emerging Hospitality Profession, the first book of its kind, focuses on the event planning at a college or university and provides broad insights on what this line of work can offer both personally and professionally. This digital text also introduces students to the professional opportunities in the meeting, incentive, conference, and exposition industry (M.I.C.E.). Features of Event Planning & Management At Colleges & Universities include: Chapter Discussion Boards Chapter Assignments External Links Grade Book
Keywords: dept.rec

Acculturation Processes of International Labour in Switzerland in the Hospitality Organisations - Ermolaeva, P.; Sisson, A.D. (African Journal of Hospitality, Tourism and Leisure, 2023)
The following research examines the acculturation processes of migrants, working in Switzerland, particularly in the hospitality industry. Due to rapid globalisation and lack of investigation on worker’s adaptation, there remains a gap in the research based on the employees’ cultural clash occurrence. The study explores potential tools which might simplify cultural adaptation and provide a better understanding of international communication for any future employees coming to live and work in Switzerland. Semi-structured interviews with participants from different nationalities were conducted to identify the importance of effective acculturation, the adaptation issues, and the influence of those on work and life in Switzerland. The results demonstrate that the most efficient way to acculturate in Switzerland is integration to the culture and traditions of the country and its history through understanding their values, norms, practices. Moreover, Switzerland was viewed as a very conservative and strict country where one must work hard to be accepted. Those participants who tried to separate, assimilate, or marginalise tend to experience tougher acculturation. Language, namely Swiss German or German, was highlighted as the most essential to learn or to be provided by the workplace. Lastly, current research identified a link between successful acculturation with job opportunities and development. Since salaries and job opportunities are not the same for the foreign workers in comparison to Swiss employees on the same position there might be a potential recommendation for improvement. Little to no link has been found between acculturation and psychological well-being, financial status, and health conditions. © 2023 AJHTL /Author(s)
Keywords: Hofstede’s framework; acculturation; adaptation; dept.rec; international labour; migrant workers; peer-reviewed; ⚠️ Invalid DOI

Development of a Schoolwide Behavioral Support Plan for East Hartford High School. - Cipriano, Robert E. (2004)
Keywords: dept.rec; faculty_collection; sabbatical_report

Leadership Development: An Experiential Approach. - Shattuck, J. Bruce (Spring;Recreation/Leisure., 1997)
Keywords: dept.rec; faculty_collection; sabbatical_report

Analysis of the Best Professional Practices in Therapeutic Recreation. - Cipriano, Robert E. (1992)
Keywords: dept.rec; faculty_collection; sabbatical_report

Common Characteristics of Successful Public Park and Recreation Delivery Systems. - O'Sullivan, Ellen (1990)
Keywords: dept.rec; faculty_collection; sabbatical_report

A Toolkit for College Professors - Buller, Jeffrey L.; Cipriano, Robert E. (Rowman & Littlefield, 2015)
Keywords: College teaching; Handbooks, manuals, etc; Handbooks, manuals, etc; College teachers; Professional relationships; dept.rec; faculty_collection

Facilitating a Collegial Department in Higher Education: Strategies for Success - Cipriano, Robert E. (Jossey-Bass resources for department chairs, 2011)
"Collegiality is a key element that department chairs value when recommending faculty members for tenure. This practical book (written for chairs and deans) offers a reference of "what to do" proactively so that departments function effectively. The book is filled with the most current ideas and research of what has worked to enhance the climate, culture, and collegiality in the department, as well as the university. The book also includes case law relative to collegiality or lack of collegiality in higher education so that readers will get a helpful guide to nurturing a more collegial department--in a way, preventing toxic situations from arising or worsening"--
Keywords: Administration; United States; Universities and colleges; dept.rec; faculty_collection

Heartfelt: A Journey Through Transplantation - Panza, Joseph (iUniverse, 2009)
This is the remarkable, moving true story of two families brought together through tragedy and triumph. One loses a family member; one regains a life. See how it happens, as it happens. Be there at bedside, through the waiting, through the wondering as Joe brings you through the days, weeks and months leading up to and following his wife Jean's transplant. Learn how circumstances beyond anyone's direct control come to intersect, changing forever all those who experience it from their own perspectives spoken in first person language.
Keywords: Heart; Patients; Transplantation of organs, tissues, etc; Transplantation; dept.rec; faculty_collection

Vandalism in Public Park Facilities: A Guide for Park Managers - Shattuck, J. Bruce (Publishing Horizons, 1987)
Keywords: Maintenance; Maintenance; Parks; Parks; United States; United States; Parks; Vandalism; Vandalism; Parks; dept.rec; faculty_collection

Readings in Special Olympics - Cipriano, Robert E. (Special education series (Guilford, Conn.), 1980)
Keywords: Special Olympics; Sports for people with mental disabilities; dept.rec; faculty_collection

Jumping for Joy - Ryan, Frank; Hall, Elizabeth T. (Scribner, 1980)
Discusses the history and techniques of the four jumps featured in track and field events: the high jump, the pole vault, the long jump, and the triple jump.
Keywords: Jumping; Juvenile literature; dept.rec; faculty_collection

Slimnastics Is Fun - Jones, MG Sholtis (Leisure Services Publications, 1976)
Keywords: Exercise; dept.rec; faculty_collection

Me Is How I Feel: Poems, - Crossen, Stacy Jo; Covell, Natalie Anne; De Larrea, Victoria (McCall Pub. Co, 1970)
Thirteen poems about such emotions as happiness, frustration, anger, pride, loneliness, love, and disappointment.
Keywords: dept.rec; faculty_collection

Illustrated Guide to Championship Football, - Kapral, Frank S. (Parker Pub. Co, 1967)
Keywords: Football; Pictorial works; dept.rec; faculty_collection

A Method for Teaching Creative Dance. - Barrow, Billie (Bartlett Hofman, 1961)
Keywords: Dance; Study and teaching; dept.rec; faculty_collection

Ayres Sensory Integration® for Addressing Play in Autistic Children: A Multiple-Baseline Examination - Kuhaneck, Heather M.; Watling, Renee; Glennon, Tara J. (The American Journal of Occupational Therapy, 2023)
Importance: Play is an area of difficulty for autistic children, and occupational therapy practitioners need evidence to guide interventions to improve play for this population. Ayres Sensory Integration® (ASI) intervention has not yet been studied for its impact on play outcomes.Objective: To examine the impact of ASI intervention on play types in autistic children.Design: Nonconcurrent, multiple-baseline design across subjects.Setting: Outpatient occupational therapy clinic in New England.Participants: Three autistic children, ages 5, 6, and 6 yr.Intervention: Twenty-four ASI sessions.Outcomes and Measures: Frequency of play type was coded using partial interval coding. Progress monitoring used Goal Attainment Scaling.Results: All three participants demonstrated changes in the frequency of specific types of play, but changes varied among them.Conclusions and Relevance: Findings suggest that ASI intervention may alter a child’s patterns of play.What This Article Adds: This study is the first to examine the impact of ASI on play and the third that documents the feasibility of single-subject research for studying ASI. If confirmed in future studies, ASI could become an evidence-based intervention for improving play, an important outcome for autistic children and the profession of occupational therapy.Positionality Statement: This article uses the identity-first language autistic people. This nonableist language describes their strengths and abilities and is a conscious decision. This language is favored by autistic communities and self-advocates and has been adopted by health care professionals and researchers (Bottema-Beutel et al., 2021; Kenny et al., 2016).
Keywords: dept.rec; peer-reviewed

Father–child playfulness: a secondary analysis of a multiple-baseline single-subject study of three children with autism spectrum disorder - Waldman-Levi, Amiya; Kuhaneck, Heather (The American Journal of Occupational Therapy, 2023)
Importance: Ayres Sensory Integration® (ASI) is commonly used with children on the autism spectrum to promote sensory processing and improved occupational performance, including play. To date, there has been no explicit effort to examine improvements in playfulness through ASI.Objective: To explore whether ASI, coupled with parent training, improves child playfulness and fathers’ support of child playfulness.Design: Single-subject A–B–BC design secondary analysis of a nonconcurrent multiple-baseline study.Setting: Occupational therapy clinic.Participants: Three father–child dyads; children were ages 3 to 6 yr, with autism spectrum disorder (ASD) and documented sensory processing concerns.Intervention: After a baseline phase, each child received at least 24 sessions of ASI, and fathers received parent training focusing on sensory processing issues and play via an online presentation.Outcomes and Measures: The Parent/Caregiver’s Support of Children’s Playfulness and the Test of Playfulness.Results: Visual analysis of the baseline phase, ASI phase, and ASI with parent training phase shows that all 3 fathers demonstrated an increase in the way they supported their child’s playfulness; however, this change was not maintained. Children’s playfulness fluctuated, reaching a peak after fathers received training, but none of the children maintained that change.Conclusions and Relevance: Additional support by the therapist is required for fathers to learn and use new strategies to promote consistent change in child playfulness during play. Pilot data can be used to inform future studies.What This Article Adds: Occupation- and family-centered frameworks may be useful in guiding practice when working with families of children with ASD.
Keywords: dept.rec; peer-reviewed

Getting back to human touch: habit and change decisions during mobile device intermediations at events - Sisson, A.; Whalen, E. (Consumer Behavior in Tourism and Hospitality, 2023)
Purpose: As mobile device use in the events industry increases worldwide, an essential component for successful events is creating a unique experience. One way to enhance entertainer and attendee experience is by offering a phone-free space to enjoy an event. This study aims to examine mobile device habits and attendee willingness to adopt a mobile locking mechanism product at events and festivals. Design/methodology/approach: Analysis of variance and regression analyses were used to test the research questions using data collected from 299 attendees recruited through an online research company. Findings: Results reveal that mobile device habits are significantly related to the adoption of the phone locking product at events. Practical implications: This study provides contributions to event planners to offer distraction-free settings that provide an overall escapist experience for attendees. Originality/value: To the best of the authors’ knowledge, this study is among the first to empirically examine the role of mobile device habits and willingness to adopt a phone-locking device with event attendees. © 2022, Emerald Publishing Limited.
Keywords: Decision-making; Events and festivals; Habit; Mobile device use; dept.rec; peer-reviewed

Leadership skills with classroom instruction integration in hospitality management higher education - Sisson, A.D.; Roberts, K.R. (Journal of Teaching in Travel and Tourism, 2022)
To move from the gap between industry and academia, educators must review and change instructional content to meet industry demands. By addressing the industry imperative for leadership skills, this exploratory study evaluates the most prominent leadership style among faculty who implement leadership pedagogy in the classroom. The researchers surveyed hospitality management faculty through an online survey. The majority of respondents identified as transformational leaders, indicating leadership integration as highly important. The two most frequently integrated instruction methods were student-led discussions and delegation of group tasks. No significant relationship existed between methods of leadership integration and leadership style. Findings from this research contribute how educational leaders influence leadership skills and competency integration in classroom instruction. Recommendations included conducting further studies of hospitality management educators’ leadership styles, enhanced statistical tests to build significant results to methods of transformation leadership in classroom instruction, and effective leadership training for hospitality management educators and administrators. © 2022 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Leadership style; classroom instruction; dept.rec; educational leaders; hospitality faculty; integration; peer-reviewed

Natural environment disaster survival experiences: Narrative research from two communities - Prince, M.; Davies, M.A.P. (Australasian Journal of Disaster and Trauma Studies, 2007)
We develop a model of sequential responses of disaster survivors as they experience natural disaster stages. The disaster response model is based on the confluence of psychological processes with temporal environmental states that are markers of disaster periods. The study analyzes journalistic narratives taken from informants experiencing natural disasters in two culturally diverse communities. Recorded short-term vivid memory traces of survivors are assumed to accurately project their interpretations of events and experiences, reflected in their narratives. Whilst survivors share many similarities in their profiles of natural disaster response, some cultural differences in response are observed between communities, such as religiosity. Copyright © 2007 Massey University.
Keywords: Culture; Disaster survivors; Flood; Narrative research; Tsunami; dept.mkt; ⛔ No DOI found

Athlete welfare and protection policy development in the USA - Lopiano, D.A.; Zotos, C. (Safeguarding, Child Prot. and Abuse in Sport: Int. Perspect. in Res., Policy and Pract., 2014)
Keywords: dept.rec

Exploratory study on the perceptions of event gamification on positive behavioral outcomes - Sisson, Annamarie D.; Whalen, Elizabeth A. (Journal of Hospitality and Tourism Insights, 2021)
Purpose The value of the events industry is increasing worldwide. An essential component for successful events is creating a unique experience by offering gamification. A conceptual model is proposed, exploring pre-event game communication and its effect on attendees' value perceptions, willingness to participate, word of mouth intentions and emotional commitment during gameplay at conference events. Design/methodology/approach Analysis of variance and structural equation modeling were employed to test the model using data collected from 177 attendees recruited from hospitality and tourism association network listservs and online research company. Findings Results reveal that perceptions of event gamification increase word of mouth intentions, willingness to participate and emotional commitment. Practical implications The study contributes to the knowledge of conference events with recommendations for incorporation of game elements for meeting planners to enhance attendee behaviors at the event. Originality/value This study is among the first to examine positive behavioral outcomes of using games at conference events.
Keywords: Emotional commitment; Events; Gamification; Self-determination; Theory of belongingness; Value; Willingness to participate; Word of mouth; dept.rec; peer-reviewed

Music festival supervisor leadership style and organizational citizenship behavior: the effects of employee and volunteer relationships and dependence on their leader - Sisson, A.D. (International Journal of Event and Festival Management, 2021)
Purpose: The relationship between leadership style and employee outcomes is well established. However, organizational management research lacks an understanding of the dyadic relationship between supervisors and employees and volunteers at music festivals. This study examines a mediation model in which leader–member exchange (LMX) affects leadership style and organizational citizenship behavior. Additionally, the study examines a moderating model in which dependence on the leader moderates relationships between leadership style and leader–member exchange. Design/methodology/approach: Confirmatory factor analysis, structural equation modeling and conditional process analysis were employed to test the model using data collected from 97 supervisors, volunteers and employees who worked at an annual large-scale music festival staged in Costa Rica. Findings: Results reveal that leadership style relates positively to LMX and organizational citizenship behavior (OCB). Simultaneously, the mediating effect of LMX and moderating effect of dependence on the leader was not significant on the leadership style and OCB. Research limitations/implications: Given the small sample size and accessibility to one music festival, caution should be taken in drawing causal conclusions from the results. Practical implications: The study contributes to the knowledge of event and festival management with recommendations for leadership training initiatives for supervisors and employees/volunteers. Originality/value: This study is among the first to examine the mediating role of LMX between leadership style and OCB, moderating the role of dependence on leadership style and LMX with music festival supervisors and employees/volunteers. © 2021, Emerald Publishing Limited.
Keywords: dept.rec; peer-reviewed

How was your music festival experience? Impacts on loyalty, word-of-mouth, and sustainability behaviors - Sisson, Annamarie D.; Alcorn, Michelle (Event Management, 2021)
As the popularity of music festivals increases worldwide, an essential component for successful festivals is creating an exceptional guest experience. A conceptual model is proposed, positing that experience economy has a positive effect on loyalty, word-of-mouth (WOM) intentions, and sustainability behaviors of event attendees at a music festival that focuses on sustainability. Multiple regression and structural equation modeling (SEM) were employed to test the model using data collected from 216 attendees at an annual music festival staged in Costa Rica. Results reveal that experience has a positive effect on sustainability behaviors. Additionally, some dimensions of the experience economy have a positive impact on WOM intentions and loyalty. Lastly, WOM intentions have a positive effect on sustainability behaviors. The study provides vital contributions to planning and managing sustainable music festival events. Music festival planners and marketing teams are recommended to offer activities that provide an overall positive experience.
Keywords: EXPERIENCE ECONOMY; LOYALTY; MUSIC FESTIVALS; SUSTAINABILITY BEHAVIORS; WORD-OF-MOUTH; dept.rec; peer-reviewed

No internship? No problem! - Milone, Joseph P.; Archambault, MaryJo (SCHOLE: A Journal of Leisure Studies and Recreation Education, 2021)
The pandemic created obstacles for our therapeutic recreation students who could not find or participate in an in-person internship. The only viable option was to create a virtual internship experience that still met NCTRC standards for national certification. This learning activity details the steps taken to create the experience, what was successful, and lessons learned.
Keywords: dept.rec; peer-reviewed

Collaborating With Parks and Recreation Departments to Address Youth Health - Risisky, Deb; MacGregor, James (Health Promotion Practice, 2021)
Adolescence is an important time for addressing health, including mental health, obesity, substance use, and food insecurity. As the myriad health and wellness needs of community members expands, it becomes increasingly difficult for one profession alone to address these needs. The park and recreation field was founded to address the health and wellness needs of people, and much of their programming is focused on youth. Thus, municipal park and recreation departments are becoming increasingly involved in collaborative partnerships with other health-serving agencies within their community. This study explored park and recreation directors’ experiences in collaborating with health agencies to better address health and wellness factors that affect the youth in their communities. This phenomenological qualitative study employed in-depth interviews with park and recreation directors and used thematic analysis. Nine interviews were conducted from four of the six New England states. The most common health concern seen by the directors was mental health, primarily behavioral health challenges. Parks and recreation collaboration with public health organizations ranged from none to close collaborations; directors regularly spoke about wanting to strengthen their collaborations. Public health and park and recreation staff have similar challenges with staffing and resources; additionally, they have complimentary skills with regard to planning and implementing health-related programs. For that reason, creating purposeful collaborative partnerships between public health agencies and park and recreation departments, focused on measurable outcomes, may increase benefits to the health of youth in a community.
Keywords: adolescent health; collaboration; dept.pch; dept.rec; mental health; multisector; park and recreation; peer-reviewed; physical activity; prevention; trauma

Changing college student perceptions of individuals with disabilities using contact theory and community-based recreation activities - Archambault, MaryJo; Milone, Joseph P. (SCHOLE: A Journal of Leisure Studies and Recreation Education, 2020)
Keywords: dept.rec; peer-reviewed

Relax and run - Myerson, Sandra H (Journal of Physical Education and Recreation, 1979)
Keywords: dept.rec

College Football and Social-Mobility - Case-Study of Notre-Dame Football Players - Sack, AL; Thiel, R (Sociology of Education, 1979)
Keywords: dept.rec

Locus of control among Dutch and American women softball players. - Finn, Joan A; Straub, William F (Research Quarterly. American Alliance for Health, Physical Education and Recreation, 1977)
Locus of control is a personality variable that manifests itself through an individual’s perception of the reinforcement he receives. This belief system is based on a continuum ranging from the perception that rewards are completely contingent upon one’s behavior to the belief that only luck, chance, or fate control one’s life. This construct has received considerable attention within the realm of psychology, but is conspicuous by its absence in sport and physical education literature. The purpose of this study was to compare the locus of control of highly skilled Dutch (N = 35) and American (N = 44) women softball players. The Rotter internal-external locus of control scale was utilized to determine internal-external orientations of the subjects. Data were analyzed by using ANOVA and product moment correlations. Statistically significant (.01 level) differences in locus of control were found. American women softball players were significantly more internally oriented than were their Dutch counterparts. © 1977 Taylor 8 Francis Group, LLC.
Keywords: Adolescent; Adult; Baseball; Comparative Study; Cross-Cultural Comparison; Female; Human; Male; Netherlands; Personality; Sports; United States; adolescent; adult; article; baseball; comparative study; cultural factor; dept.rec; female; human; male; personality; sport

Julian smith 1901–1975 - Donaldson, George W.; George, Jack F. (Journal of physical education and recreation, 1975)
Keywords: dept.rec

A report from the NFHPER board of directors - George, Jack (Journal of health,physical education and recreation, 1972)
Keywords: dept.rec

The masters program in physical education with a specialization in physical education-recreation for the handicapped - Bonis, Edith De (Journal of health,physical education and recreation, 1971)
Keywords: dept.rec

A poem reflecting the philosophic attitudes of the naturalistic movement in physical education - Hatfield, Frederick C (Quest, 1969)
Keywords: dept.rec

Comparison of skeletal age and various physical and motor factors with the pubescent development of 10,13, and 16 year old boys - Clarke, H Harrison; Degutis, Ernest W (Research Quarterly. American Association for Health, Physical Education and Recreation, 1962)
The purpose of this study was to compare the skeletal ages and various physical and motor factors with the pubescent development of 10, 13, and 16 year old boys. The findings of this study indicated that physical maturation was differentiated most effectively at 13 years of age, although it was not so sensitive to maturational changes as was skeletal age; at 16 years, maturational differentiation was much more limited; and at 10 years, little or no value can be attributed to this method. The 13 and 16 year old boys who were advanced in pubescent development had higher mean scores on all physical and motor tests studied with few exceptions; generally, the differences between the means were significant. In terms of physique types, the only significant difference was found at 16 years of age, where a greater percentage of ectomorphs was found in pubescent group 4 than in group 5. © 1962 Taylor & Francis Group, LLC.
Keywords: dept.rec

Of major interest: A page for students and student major clubs: seniors: would I hire you? - Debonis, Edith (Journal of health,physical education and recreation, 1962)
Keywords: dept.rec

Preparing students to make a difference: community asset mapping as a vehicle for involving students in community action - Smith, Deborah (Schole: A Journal of Leisure Studies and Recreation Education, 2003)
Keywords: dept.rec; peer-reviewed

Stress coping mechanisms in elderly adults: an initial study of recreational and other coping behaviors in nursing home patients - Hunter, I Roy; Gillen, Mark C (Adultspan Journal, 2009)
Residents (N = 32) of 3 skilled nursing homes participated in a study designed to document the nature of the stressors they experienced and the coping mechanisms they used. Medical issues were the most common stressors. The most common coping responses were prayer, reading, watching television, listening to music, and talking to friends and family. © 2009 by the American Counseling Association. All rights reserved.
Keywords: dept.rec

An analysis of whitewater rafting safety data: risk management for programme organizers - Hunter, I. Roy (Journal of Adventure Education & Outdoor Learning, 2007)
Keywords: dept.rec

Alcohol as a response to stress in older adults: A counseling perspective - Hunter, I Roy; Gillen, Mark C (Adultspan Journal, 2006)
Keywords: dept.rec

The role of ego threat in professional growth: Fulfilling the ethical intentions of the SEED Model - Gregory, Jess L.; Mebane, Karreem A. (Educational Practice and Theory, 2020)
Schools and education in general have made an implicit and, we would assert, explicit promise to society to educate all the children in their care. Unfortunately, there are achievement gaps that illustrate how schools have broken this promise. Teacher evaluation and other accountability measures have been heralded as the answer to this problem. Educator ego threat impedes the implementation of goal-driven teacher evaluation models and, thus, ethical questions arise. To realize the noble goals of educator evaluation, leaders must attend to ethical concerns and to the human aspects of ego threat.
Keywords: Educational leadership; Ego threat; Goal-setting models; Teacher evaluation; Teacher performance; dept.edl; dept.rec; peer-reviewed

Lessons learned from COVID-19: Being known in online social work classrooms - Smoyer, Amy B; O’Brien, Kyle; Rodriguez-Keyes, Elizabeth (International Social Work, 2020)
This article presents findings from a survey of undergraduate social work (Bachelor of Social Work [BSW]) students about their experiences with remote learning during the 2020 COVID-19 pandemic. In response to this crisis, remote learning was rapidly implemented and many BSW educators and students experienced online classrooms for the first time. Findings from this study shed light on how remote learning shapes the interpersonal relationships and communication that are so critical to building students’ sense of classroom belonging, engagement, and learning.
Keywords: dept.hls; dept.rec; dept.swk; peer-reviewed

Book Review: Responsible tourism - Jones, Jan L. (Annals of Tourism Research, 2013)
Keywords: book.review; dept.rec

“Smile for me Jamaica”: A snapshot of Kingston’s destination image and the need for a collaborative marketing approach - Jones, Jan Louise; Hyde, Ashley (Revista Turismo & Desenvolvimento, 2014)
Keywords: dept.rec; ⛔ No DOI found

Volunteer tourism in the global South - Jones, Jan Louise (Journal of Tourism and Cultural Change, 2016)
Keywords: dept.rec

Rating faculty collegiality - Cipriano, Robert E; Buller, Jeffrey L (Change: The Magazine of Higher Learning, 2012)
Keywords: dept.rec

Dimensions of burn survivor distress and its impact on hospital length of stay: A national institute on disability, independent living, and rehabilitation research burn model system study. - O'Brien, Kyle H (Burns : journal of the International Society for Burn Injuries, 2020)
OBJECTIVE: Guided by the Transactional Model of Stress and Coping, this study seeks to (1) examine the independent relationships between the level of distress among burn survivors, pre-morbid psychiatric history, and burn severity on length of hospital stay, and (2) to examine the relationship between having a premorbid psychiatric history and level of distress following a burn injury., METHODS: Data collected by the National Institute on Disability, Independent Living, Rehabilitation Research funded Burn Model System (N = 846) was used to theoretically link psychological distress with the length of hospital stay for survivors of burn injuries. Structural Equation Modeling was used to evaluate the aims of this study., RESULTS: Although counterintuitive, and while significant, burn severity was found to have a rather modest association with a burn survivor's level of distress, indicating that one's ability to cope may be a better predictor of distress rather than burn severity alone. Premorbid psychiatric history was significantly associated with increased levels of distress. While burn severity was associated with length of stay, level of distress did not act as a partial mediator. Length of stay was, however, significantly related to having a premorbid-psychiatric history. Of notable interest, a significant racial, ethnic, and gender difference exists in level of distress. Women and people of color experience higher levels of distress holding constant burn severity and psychiatric history., CONCLUSION: A need exists to assess for and address premorbid and current mental health challenges of burn survivors, specifically the ability to cope, especially among people of color and women, regardless of the burn size or severity. Copyright © 2019 Elsevier Ltd and ISBI. All rights reserved.
Keywords: *Adaptation, Psychological; *Burns/px [Psychology]; *Length of Stay/sn [Statistics & Numerical Data]; *Mental Disorders/px [Psychology]; *Psychological Distress; *Stress, Psychological/px [Psychology]; Adaptation, Psychological; Adolescent; Adult; African American; African Americans; African Americans/px [Psychology]; African Americans/sn [Statistics & Numerical Data]; Aged; Aged, 80 and over; Article; Body Surface Area; Burn survivors; Burns; Burns/ep [Epidemiology]; Burns/pa [Pathology]; Burns/pp [Physiopathology]; Caucasian; Distress; Ethnic Groups; European Continental Ancestry Group; European Continental Ancestry Group/px [Psychology]; European Continental Ancestry Group/sn [Statistics & Numerical Data]; Female; Hispanic; Hispanic Americans; Hispanic Americans/px [Psychology]; Hispanic Americans/sn [Statistics & Numerical Data]; Humans; Integrated care; Latent Class Analysis; Length of Stay; Length of stay; Male; Mental Disorders; Mental Disorders/ep [Epidemiology]; Mental health; Middle Aged; Models, Psychological; Psychological Distress; Psychosomatic; Sex Factors; Stress, Psychological; Stress, Psychological/eh [Ethnology]; Stress, Psychological/ep [Epidemiology]; Survivors; Young Adult; adolescent; adult; aged; body surface; burn; burn survivor; coping behavior; dept.hls; dept.hms; dept.rec; distress syndrome; electric burn; ethnic group; ethnology; female; hospital discharge; hospitalization; human; latent class analysis; length of stay; major clinical study; male; mental disease; mental stress; middle aged; outcome assessment; pain severity; pathology; pathophysiology; peer-reviewed; personal experience; psychiatric treatment; psychological aspect; psychological model; psychology; scald; secondary analysis; sex factor; structural equation modeling; survivor; very elderly; wound closure; young adult

Social determinants of health: the how, who, and where screenings are occurring; a systematic review - O’Brien, Kyle H. (Social Work in Health Care, 2019)
Screening for social determinants of health allows health care teams to assess and address social factors that influence one’s health, mental health, and access to care. These social factors include poverty, health literacy, social support, exposure to trauma, food insecurity, and housing instability. The objective of this study was to examine what screening tools for social determinants of health are being used, in what contexts, and with what populations. Findings suggest that health literacy is the most commonly screened for, followed by trauma history, social support, food insecurity and housing across diverse contexts and populations. Results from this study can be used to inform providers of available screening tools and resources that can be readily utilized in practice. © 2019, © 2019 Taylor & Francis.
Keywords: Food Supply; Health Literacy; Health Services Accessibility; Health Status Indicators; Housing; Humans; Poverty; Social Determinants of Health; Social determinants of health; catering service; dept.hls; dept.rec; dept.swk; health care; health care delivery; health literacy; health status indicator; housing; human; integrated care; interprofessional practice; peer-reviewed; poverty; primary care; screening tools; social determinants of health

Examining the impact of psychological factors on hospital length of stay for burn survivors: A systematic review - O’Brien, Kyle H; Lushin, Victor (Journal of Burn Care & Research, 2019)
Recovery of burn patients may be impeded by mental health problems. By gaining a better understanding of the impact that psychological factors may have on hospital length of stay, providers may be better informed to address the complex needs of burn survivors through effective and efficient practices. This systematic review summarizes existing data on the adverse psychological factors for the length of burn patients' hospitalization, and assesses the methodological quality of the extant literature on mental health conditions of burn survivors. A literature search was conducted in four electronic databases: PubMed, PsychINFO, Science Direct, and the Cumulative Index to Nursing and Allied Health Literature. Results yielded reports published between 1980 and 2016. Methodological quality was assessed by using an 11-item methodological quality score system. Seventy-four studies were identified by search; 19 articles were eligible for analysis. Findings demonstrate paucity of evidence in the area. Reports indicate longer hospital stay among burn patients with mental health problems. Substance use was the most consistent mental-health predictor of longer hospital stay. Heterogeneity in data on mental health conditions rendered impossible estimation of effect sizes of individual psychological factors on length of hospitalization. Many studies over-relied on retrospective designs, and crude indicators of psychological factors. Findings indicate that mental health problems do have an impact on the trajectory of burn recovery by increasing the length of hospital stay for burn survivors. Inpatient mental health services for burn patients are critically needed. Prospective designs, and more sensitive psychological indicators are needed for future studies.
Keywords: Article; Burns; Hospitalization; Humans; Length of Stay; Survivors; burn; burn patient; burn survivor; dept.hls; dept.rec; dept.swk; distress syndrome; hospitalization; human; length of stay; mental disease; mental health; peer-reviewed; psychological aspect; psychology; substance use; survivor; systematic review

Promoting pro-social skills to reduce violence among urban middle school youth - Risisky, Deb; MacGregor, J; Smith, D. A.; Abraham, J; Archambault, M (Journal of Youth Development, 2019)
Adolescent violence is a significant public health problem. The goal of this evaluation was to determine whether communication skills, relationships with adults, and relationships with peers were enhanced through participating in an after-school program aimed at reducing violence-related behaviors among urban middle school youth. Elements that helped to foster success among our population were providing a program that enabled consistent choice in recreational activities in a safe place, and also providing busing home to increase safety. A non-experimental study was conducted with 115 students who participated in the program. Bivariate, ANOVA analysis, and Kruskal–Wallis tests were carried out. Results indicated that participating in the program significantly impacted student relationships with adults and their peers as well as positively impacted their communication skills. The program was designed with purposeful activities that would address pro-social behaviors, enhance youth interest, and increase attendance. The program specifically used recreation to help foster relationships with their peers and the adults in the program, with the intention of reducing conflict, and therefore violence among the students.
Keywords: After-school program; Recreation programs; Youth violence; dept.pch; dept.rec; peer-reviewed

The Power of Adapted Sports, Changing Attitudes in Higher Education: An Exploratory Study - Archambault, MaryJo; Searcy, Yan Dominic (Palaestra, 2018)
A wheelchair basketball showcase was hosted at a state university in New England. Student surveys revealed that the event had a positive effect on students’ views of both individuals with disabilities and adapted sports. Using Allport’s (1954) contact theory as a lens, the author demonstrates how the event met the four positive features that Allport believed should be present in order to reduce negative feelings toward another group: (a) equal status between the groups, (b) common goals, (c) intergroup cooperation and (d) the support of authorities. This exploratory study argues that adapted sports can be an effective method to positively impact stereotypical views of people with disabilities.Subscribe to PALAESTRA
Keywords: Adaptive sports; changing attitudes; contact theory; dept.hhs; dept.rec; higher education; peer-reviewed; ⛔ No DOI found

Retooling the health care workforce in the era of the Affordable Care Act: An evaluation of an advanced certificate program in integrated primary and behavioral health care - O’Brien, Kyle H.; Acri, Mary C.; Campanelli, Peter C.; Cerniglia, Joseph A.; McKay, Mary M. (Journal of Teaching in Social Work, 2018)
The Affordable Care Act aims to increase affordable coverage, reduce overall costs, and improve health outcomes. To achieve these aims, new knowledge and skills must be built within the existing workforce. The purpose of this article is to examine the behavioral and organizational changes brought about by an educational program that aimed to retool the healthcare workforce for the implementation of integrated primary and behavioral healthcare models, with an added emphasis on prevention. Sixty-three participants of an Advanced Certificate Program completed 1 or more evidence-informed learning modules centered on integrated primary and behavioral health care. The vast majority of students who completed each of the 5 modules of the program reported acquiring new knowledge and skills. Student satisfaction of the program met or exceeded overall expectations. In addition, program participation has resulted in not only students’ intentions to change workplace practices but also actual implementation of workplace changes related to integrated care models. The Advanced Certificate Program appears to be a promising platform for service providers to align their knowledge and skills with the premises of current healthcare reform. © 2018, © 2018 Taylor & Francis.
Keywords: Affordable Care Act; Integrated primary and behavioral health care; certificate programs; dept.rec; dept.swk; integrated care; peer-reviewed; workforce training

Barriers and facilitators to mental health screening efforts for families in pediatric primary care - Acri, Mary; Zhang, Shirley; Chomanczuk, Aminda H.; O’Brien, Kyle H; De Zitella, Maria L. Mini; Scrofani, Paige R.; Velez, Laura; Garay, Elene; Sezer, Sara; Little, Virna; Cleek, Andrew; McKay, Mary M (Journal of Family Social Work, 2018)
The purpose of this commentary was to describe the barriers and facilitators to mental health screening efforts for children between age 5 and 18 years within three primary care clinics in poverty-impacted communities as part of an integrated care model. Three screeners, two women and one male, participated in a screening effort between September and December 2015. Screeners were interviewed about their perceptions of barriers and facilitators to screening. Organizational, family, and screener-level factors were found to influence delivery of screenings to children. Given the benefits of screening in primary care settings, identifying barriers to these initiatives and ways to address them pre-emptively could potentially alter the developmental trajectory and outcomes of children at risk for serious mental health conditions. © 2018, © 2018 Taylor & Francis.
Keywords: Screening and detection efforts; article; case report; child; child mental health; clinical article; dept.rec; dept.swk; female; human; human experiment; integrated care; male; mental health; outcome assessment; peer-reviewed; perception; poverty; primary medical care

Multiple family group service delivery model for children with disruptive behavior disorders: Impact on caregiver stress and depressive symptoms - Gopalan, Geetha; Bornheimer, Lindsay A.; Acri, Mary; Winters, Andrew; O’Brien, Kyle H.; Chacko, Anil (Journal of Emotional and Behavioral Disorders, 2018)
Disproportionately high rates of caregiver stress and depression are found among poverty-impacted communities, with high levels of caregiver stress and depression putting youth at heightened risk for the onset and perpetuation of disruptive behavior disorders. The purpose of this study was to examine the effects of a behavioral parent training program called the 4Rs and 2Ss for Strengthening Families Program (4R2S) on caregiver stress and depressive symptoms among 320 youth aged 7 to 11 and their families assigned to either the 4R2S or services as usual (SAU) condition. Among caregivers with clinically significant (CS) scores at baseline, 4R2S participants manifested significantly reduced scores on the stress and depressive symptom scores to SAU participants at 6-month follow-up. Findings suggest that 4R2S may reduce caregiver stress and depressive symptoms among those caregivers initially manifesting CS levels of stress or depressive symptoms.
Keywords: dept.rec; dept.swk; peer-reviewed

National Collegiate Academic Association? The implications of increased NCAA oversight of academics - Trachsler, Tracy A.; Cotrufo, Raymond J. (Journal of Contemporary Athletics, 2017)
Keywords: dept.rec; ⛔ No DOI found